2017
DOI: 10.1093/cid/cix529
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Taper and Pulse Regimen With Careful Follow-up for Patients With Recurrent Clostridium difficile Infection

Abstract: We retrospectively studied vancomycin taper and pulse treatment on 100 consecutive, evaluable patients with recurrent Clostridium difficile infection. Following taper to once-daily vancomycin dosing, 22 of 36 patients (61%) who received every-other-day dosing (QOD) and 50 of 64 (81%) who received QOD followed by every-third-day dosing were cured (P = .03).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 11 publications
0
38
0
2
Order By: Relevance
“…Administering a relatively long taper could potentially be beneficial to provide sufficient time to eliminate residual spores from the intestinal tract. However, Sirbu et al (15) reported similar cure rates in patients receiving vancomycin taper regimens of Ͻ10 and Ͼ10 weeks in total duration. Efforts to minimize the risk for reexposure to spores after the taper may also be beneficial (e.g., environmental disinfection and patient hand hygiene and bathing).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Administering a relatively long taper could potentially be beneficial to provide sufficient time to eliminate residual spores from the intestinal tract. However, Sirbu et al (15) reported similar cure rates in patients receiving vancomycin taper regimens of Ͻ10 and Ͼ10 weeks in total duration. Efforts to minimize the risk for reexposure to spores after the taper may also be beneficial (e.g., environmental disinfection and patient hand hygiene and bathing).…”
Section: Discussionmentioning
confidence: 96%
“…Although new approaches for management of recurrent CDI are promising, oral vancomycin administered as a tapered and/or pulsed regimen remains the most common treatment strategy for second or greater recurrences of CDI (14)(15)(16). These regimens typically include a 10-to 14-day course of oral vancomycin at a dose of 125 mg four times per day, followed by a tapering dose over 2 weeks, followed by "pulsed" dosing with 125 mg once every 2 or 3 days for 2 to 8 weeks (14)(15)(16). Standard vancomycin regimens achieve persistent high concentrations in stool (1,000 to 2,000 g/g stool) and cause marked disruption of the intestinal microbiota (4)(5)(6)(7)(8)(9)17).…”
mentioning
confidence: 99%
“…Retrospective observational data suggest potential efficacy of extended-pulsed vancomycin for recurrent C difficile infection. 24 However, laboratory studies have shown the disruptive effect of vancomycin on gut microbiota, 25 and such an extended regimen could further exacerbate post-treatment gut microbiota dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…To optimize vancomycin treatment evaluated in recurrent C difficile infection, it might be possible to use a pulsed or tapered regimen of vancomycin. Evidence for this approach includes observational studies showing recurrence rates ranging from 31% to 6%100101102 and one randomized trial that included 12 patients, where the recurrence rate reached 41.7% 103…”
Section: Treatmentmentioning
confidence: 99%